Can Board Games Enhance Students’ Vocabulary Acquisition Through Narrative Texts? - Sairiyah, Mahmudatus; Hanna, Ina Daril; Qulub, Khofifatul; Kirom, Amilinal; Alyamani, Lutfiyanto; Mahmudi, Moh; Musyarrofah, Musyarrofah; Ferdiyansyah, Ferdiyansyah (DIDAKTIKA : Jurnal Penelitian Tindakan Kelas, 2025)
This study aimed to enhance students' English vocabulary through the integration of narrative texts and board games in classroom instruction. Employing a Classroom Action Research (CAR) design, the research was conducted with tenth-grade students at MA Miftahul Ulum Bettet. An initial pre-test was administered to assess students' baseline vocabulary knowledge. In Cycle 1, narrative texts and board games were introduced to facilitate contextual understanding of word meanings. Cycle 2 implemented a more interactive learning approach, encouraging students to identify and comprehend vocabulary from narrative texts while actively engaging with board games. Data collection methods included vocabulary tests, vocabulary analysis, and classroom observations. The findings revealed a consistent improvement in students’ vocabulary acquisition across the two cycles. Notably, there were significant gains in both vocabulary comprehension and retention. The study concludes that the combined use of narrative texts and board games constitutes an effective and engaging strategy for vocabulary development in English language learning.